Homicídio qualificado - Pereira, Joana Filipa Marques (2020)
After a four - month internship in DIAP the Lisbon West County where among other matters had closer contact with the especially violent and highly organized crime, decided to carry out a report on the most serious crime against life, aggravated murder. After the consultation of various processes, I realized that the way this form of crime treated at various stages of the process was different. Therefore, this report will focus on the different perspectives that may exist in the qualification of the crime, the investigation stage, when the indictment by the prosecutor, and the trial phase, upon conviction. Possible reasons for different treatment, on the one hand, differences in the interpretation of the penal code art. 132º the other hand, the probative force required in each stage, and secondly, substantial modification of facts and, first of all a framing of murder and felony murder, and only then will move to the analysis of the possible reasons of difference, leaving the end of the case analysis in concrete that passed through my hands.